SHAPING IDEOLOGIES: THE EARLY LIFE AND REVOLUTIONARY PATH OF SUBHAS CHANDRA BOSE - Bishwa Ranjan, Dr. Neeraj Kumar Singh (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Subhas Chandra Bose remains a seminal figure in India’s quest for independence, celebrated for his revolutionary zeal and strategic foresight. This paper delves into Bose's early life, psychological framework, and the environmental factors that shaped his ideologies. Raised in an affluent Bengali family, Bose's nationalist fervor was deeply influenced by the extremist nationalism of Bengal and the spiritual teachings of Swami Vivekananda and Ramakrishna Paramahamsa. The study examines Bose’s political journey, emphasizing his tenure as Congress President and the establishment of the Indian National Army (INA) highlighting his commitment to militant nationalism. Despite considerable opposition and numerous setbacks, Bose's legacy as a revolutionary leader is indelible. His initiatives spurred mass mobilization and infused a militant spirit into the Indian independence movement.